PENGARUH PENGETAHUAN TENTANG RIBA NASIAH DAN RELIGIUSITAS TERHADAP MINAT MENABUNG MAHASISWA DI BANK SYARIAH - Piolita Zulva; Sissah Sissah; G.W.I. Awal Habibah (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2024)
Knowledge of usury and religiosity is one of the influencing factors in making the decision to save at a sharia bank. There are still many students who already know about usury but still use conventional banks instead of using Sharia. This is the background to the research entitled knowledge of riba nasiah and religiosity on students' interest in saving in sharia banks. This research aims to determine the partial and simultaneous influence of knowledge of riba nasiah and religiosity on students' interest in saving in sharia banks. In this study, a descriptive quantitative method was used with 172 respondents with the technique used in sampling was Stratified Random Sampling, which is a sampling technique according to the population size in each strata, where in this study it was divided into 4 strata, namely sharia banking students, FEBI UIN Sutha Jambi semesters V, VII, IX, and XI. The data analysis techniques used in this research are data quality testing, classical assumption testing, hypothesis testing, multiple linear regression analysis, coefficient of determination and effective contribution testing. The results of the research show that: (1) It was found that partially and simultaneously there was a significant influence of the variables knowledge of riba nasiah and religiosity on students' interest in saving in sharia banks. (2) the variables of knowledge of riba nasiah and religiosity have a positive effect (move in the same direction) on students' interest in saving in sharia banks (3) the result of the Adjust R2 coefficient value is 0.492. This illustrates that the contribution of the variables of knowledge of riba nasiah and religiosity is 49.2% and the remaining 50.8% is influenced by other variables outside this research. And in terms of effective contribution, it shows that the variable knowledge of riba nasiah and religiosity contributed 49.7%. The variable with the most influence in this research is the variable knowledge of riba nasiah, which is 25.1%. From the results of this research, researchers see and realize that there are still many sharia banking study program students who use conventional banks. In fact, there are still those who don't understand about usury and religiosity even though they have studied this during lectures. Students' ignorance about usury and religiosity could be one of the factors that influence them in choosing which bank to use for savings or transactions.